Herbal medications for surgical patients: a systematic review protocol. Issue 7 (26th July 2017) - Arruda, Ana Paula Nappi; Ayala, Ana Patricia; Lopes, Luciane C; Bergamaschi, Cristiane C; Guimarães, Caio; Grossi, Mariana Del; Righesso, Leonardo A R; Agarwal, Arnav; Dib, Regina El
Abstract : Introduction: Postoperative nausea and vomiting (PONV) affect approximately 80% of surgical patients and is associated with increased length of hospital stay and systemic costs. Preoperative and postoperative pain, anxiety and depression are also commonly reported. Recent evidence regarding their safety and effectiveness has not been synthesised. The aim of this systematic review is to evaluate the efficacy and safety of herbal medications for the treatment and prevention of anxiety, depression, pain and PONV in patients undergoing laparoscopic, obstetrical/gynaecological and cardiovascular surgical procedures. Methods and analysis: The following electronic databases will be searched up to 1 October 2016 without language or publication status restrictions: CENTRAL, MEDLINE, EMBASE, CINAHL, Web of Science and LILACS. Randomised clinical trials enrolling adult surgical patients undergoing laparoscopic, obstetrical/gynaecological and cardiovascular surgeries and managed with herbal medication versus a control group (placebo, no intervention or active control) prophylactically or therapeutically will be considered eligible. Outcomes of interest will include the following: anxiety, depression, pain, nausea and vomiting. A team of reviewers will complete title and abstract screening and full-text screening for identified hits independently and in duplicate. Data extraction, risk of bias assessments and evaluation of the overall quality of evidence for each relevant outcome reported will be conducted independently and in duplicate using the Grading of Recommendations Assessment Development and Evaluation classification system. Dichotomous data will be summarised as risk ratios; continuous data will be summarised as standard average differences with 95% CIs. Ethics and dissemination: This is one of the first efforts to systematically summarise existing evidence evaluating the use of herbal medications in laparoscopic, obstetrical/gynaecological and cardiovascular surgical patients. The findings of this review will be disseminated through peer-reviewed publications and conference presentations. Systematic review registration: PROSPERO CRD42016042838.